Nursing Intervention Model to Overcome Psychosocial Problems of Breast Cancer Patients: A Literature Review - Henri Setiawan; Suharta Suharta; Ishana Balaputra; Nur Hidayat; Heri Ariyanto; Andan Firmansyah (Journal of International Conference Proceedings, 2022)
Chronic disease, such as breast cancer is a disease that requires comprehensive treatment and takes a long time. The prevalence of breast cancer patients continues to be high in number so that it will cause psychosocial problems such as social problems, anxiety, and even depression. This study aims to identify appropriate nursing interventions to address psychosocial problems in breast cancer patients. literature review was used in this study. Article searches were conducted in six journal databases, namely PubMed, JSTOR, Taylor, Willey Online, Sage, and Google Scholar. Seven articles were found that matched the inclusion of criteria. Results of this review show that social support interventions, palliative support, psychological interventions, home care, home visits, virtual reality and music therapy, relaxation techniques and motivational support, psychological therapy programs via offline and telephone, Adapted Physical Activity and Diet (APAD), Aromatherapy Plus Music Therapy can be performed on cancer patients to help reduce psychosocial problems so that the patient's quality of life will improve.